Eksplorasi Karakteristik Siswa, Budaya Sekolah, Proses Pembelajaran dan Kompetensi Guru: Studi Kasus di SMA Negeri 1 Sunggal dan MAS YASPI Labuhan Deli - Amanda, Jesica; Rahmadina, Laila; Galang, Izza; Geovani, Jen; Wantri, Joko; Nurkadri, Nurkadri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Introduction to School Field Experience (PLP) I is the initial stage in the process of introducing school field experience in the Education bachelor's program. The aim is to observe student characteristics, school culture, teaching processes, and teacher competencies. Data collection for this research is done through direct observation and using questionnaires. The research results show that there are efforts made in developing student character, implementing a positive school culture, conducting effective teaching processes, and having teachers with appropriate competencies.